Contractarianism: Morality, Rationality, and the Context of Choice - Michael Moehler (Œconomia, 2023)
This article discusses the use of orthodox rational choice theory in the context of moral contractarianism. The article’s goals are threefold. First, the article clarifies the nature of moral contractarianism and corrects a fundamental misconception. Second, it responds to criticism that follows from this misconception. It shows that the criticism either misconstrues the nature of moral contractarianism or does not apply. Third, the article clarifies the limited role that formalization can play in the context of moral contractarianism. At best, such formalization complements and, at worst, distracts from the true nature of the theory and, more generally, from the central role that the context of choice plays for the justification of moral principles in contractarian moral theory.